Le repliement des protéines : seconde traduction du message génétique - Goldberg, Michel (M/S : médecine sciences)

(untitled) (SRMS: Société de la revue médecine/sciences, 2005)
SummaryTranslation of the message encoded in a gene proceeds in two steps: one translates the gene's base sequence into the protein's aminoacid sequence; the second translates the latter into a complex, very precisely defined folded structure, the single one endowed with the specific biological properties. The second step, named « protein folding », is currently a central issue in biological research. The present editorial introduces a series of articles dedicated to this problem. It gives a brief historical overview of how our understanding of the folding mechanisms has evolved, which will be described in more details by J. Yon-Kahn. It also places the problem of protein folding in the context of basic research and its applications in several domains: (1) medicine, where folding diseases (reviewed by G. Grateau) and in particular neurodegenerative diseases caused by prions (see article by R. Melki), are more and more recognized as a public health issue ; (2) biotechnology, where the production of recombinant proteins for research, diagnostic or therapy purposes is often hampered by misfolding when a protein is expressed at high concentration in a foreign host (modern approaches to overcome this difficulty will be discussed by J.M. Betton and A. Chaffotte, and the way in which « chaperones » prevent misfolding in the cell under natural conditions will be described by A.P. Arrigo) ; (3) postgenomics, where the interpretation of the immense amount of base-sequence information collected through genome sequencing needs to be translated as rapidly as possible into structural and functional information (the computer approaches used to predict the 3D structure of a protein from its aminoacid sequence will be outlined by T. Simonson). This series comes timely, at a moment when the efforts of experimentalists, theoriticians, and « users » of protein folding start converging, and boost the power of molecular biology.